On the chronological structure of the solutrean in Southern Iberia - Cascalheira, João (2018)
The Solutrean techno-complex has gained particular significance over time for representing a clear demographic and techno-typological deviation from the developments occurred during the course of the Upper Paleolithic in Western Europe. Some of Solutrean's most relevant features are the diversity and techno-typological characteristics of the lithic armatures. These have been recurrently used as pivotal elements in numerous Solutrean-related debates, including the chronological organization of the techno-complex across Iberia and Southwestern France. In Southern Iberia, patterns of presence and/or absence of specific point types in stratified sequences tend to validate the classical ordering of the techno-complex into Lower, Middle and Upper phases, although some evidence, namely radiocarbon determinations, have not always been corroborative. Here we present the first comprehensive analysis of the currently available radiocarbon data for the Solutrean in Southern Iberia. We use a Bayesian statistical approach from 13 stratified sequences to compare the duration, and the start and end moments of each classic Solutrean phase across sites. We conclude that, based on the current data, the traditional organization of the Solutrean cannot be unquestionably confirmed for Southern Iberia, calling into doubt the status of the classically defined type-fossils as precise temporal markers.